Glucose Respiration in the Intact Chloroplast of Chlamydomonas reinhardtii - Chen, Changguo (1991)
Chloroplastic respiration was monitored by measuring (14)CO(2) from (14)C glucose in the darkened Chlamydomonas reinhardtii F-60 chloroplast. The patterns of (14)CO(2) evolution from labeled glucose in the absence and presence of the inhibitors iodoacetamide, glycolate-2-phosphate, and phosphoenolpyruvate were those expected from the oxidative pentose phosphate cycle and glycolysis. The K(m) for glucose was 56 micromolar and for MgATP was 200 micromolar. Release of (14)CO(2) was inhibited by phloretin and inorganic phosphate. Comparing the inhibition of CO(2) evolution generated by pH 7.5 with respect to pH 8.2 (optimum) in chloroplasts given C-1, C-2, and C-6 labeled glucose indicated that a suboptimum pH affects the recycling of the pentose phosphate intermediates to a greater extent than CO(2) evolution from C-1 of glucose. Respiratory inhibition by pH 7.5 in the darkened chloroplast was alleviated by NH(4)Cl and KCl (stromal alkalating agents), iodoacetamide (an inhibitor of glyceraldehyde 3-phosphate dehydrogenase), or phosphoenolpyruvate (an inhibitor of phosphofructokinase). It is concluded that the site which primarily mediates respiration in the darkened Chlamydomonas chloroplast is the fructose-1,6-bisphosphatase/phosphofructokinase junction. The respiratory pathways described here can account for the total oxidation of a hexose to CO(2) and for interactions between carbohydrate metabolism and the oxyhydrogen reaction in algal cells adapted to a hydrogen metabolism.